The use of a mini‐ridge filter with cyclotron‐based pencil beam scanning proton therapy. Issue 4 (15th February 2023) - O'Grady, Fionnbarr; Janson, Martin; Rao, Avani D.; Chawla, Ashish K.; Stephenson, Lisa; Fan, Jiajin; Wang, Peng
Abstract: Background: Pencil beam scanning (PBS) proton therapy allows for far superior dose conformality compared with passive scattering techniques. However, one drawback of PBS is that the beam delivery time can be long, particularly when treating superficial disease. Minimizing beam delivery time is important for patient comfort and precision of treatment delivery. Mini‐ridge filters (MRF) have been shown to reduce beam delivery time for synchrotron‐based PBS. Given that cyclotron systems are widely used in proton therapy it is necessary to investigate the potential clinical benefit of mini‐ridge filters in such systems. Purpose: To demonstrate the clinical benefit of using a MRF to reduce beam delivery time for patients with large target volumes and superficial disease in cyclotron‐based PBS proton therapy. Methods: A MRF beam model was generated by simulating the effect of a MRF on our clinical beam data assuming a fixed snout position relative to the isocenter. The beam model was validated with a series of measurements. The model was used to optimize treatment plans in a water phantom and on six patient DICOM datasets to further study the effect of the MRF and for comparison with physician‐approved clinical treatment plans. Beam delivery time was measured for six plans with and without the MRF to demonstrate the reduction achievable. Plans with and without MRF were reviewed to confirm clinical acceptability by a radiation oncologist. Patient‐specific QA measurements were carried out with a two‐dimensional ionization chamber array detector for one representative patient's plan optimized with the MRF beam model. Results: Results show good agreement between the simulated beam model and measurements with mean and maximum deviations of 0.06 mm (0.45%) and 0.61 mm (4.9%). The increase in Bragg peak width (FWHM) ranged from 2.7 mm at 226 MeV to 6.1 mm at 70 MeV. The mean and maximum reduction in beam delivery time observed per field was 29.1 s (32.2%) and 79.7 s (55.3%). Conclusion: MRFs can be used to reduce treatment time in cyclotron‐based PBS proton therapy without sacrificing plan quality. This is particularly beneficial for patients with large targets and superficial disease such as in breast cancer where treatment times are generally long, as well as patients treated with deep inspiration breath hold (DIBH).